Relaxin inhibits 177Lu-EDTMP associated cell death in osteosarcoma cells through notch-1 pathway - Xu Junhua; Wan Song; Chen Wei; Zhang Yi; Ji Zhenzhong (Acta Pharmaceutica)
177Lu-EDTMP (Ethylenediamine tetramethylene phosphonic acid) is the most used radioactive agent for pain palliation in bone cancer patients. The present study aims to study the impact of relaxin-2 on the 177Lu-EDTMP associated cell toxicity and death in osteosarcoma cells. MG63 and Saos-2 cells were cultured with 177Lu-EDTMP (37 MBq) for 24 h with and without pretreatment of recombinant relaxin 2 (RLXH2) for 12 and 24 h. 177Lu-EDTMP associated cellular deterioration and death was determined by LDH, MTT, and trypan blue dye assays. ELISA-based kit was used to determine apoptotic DNA fragmentation. Western blotting was used to determine expression levels of apoptotic-related signalling pathway proteins like bcl2, poly(ADP-ribose) polymerase (PARP), and MAPK (mitogen-activated protein kinase). Our results found that RLXH2 counters 177Lu-EDTMP associated cellular toxicity. Similarly, RLXH2 was able to counter 177Lu-EDTMP induced cell death in a concentration and time--dependent manner. Furthermore, it was found that RLXH2 treatment prevents apoptosis in 177Lu-EDTMP challenged cells through activation of the notch-1 pathway in a concentration- and time-dependent manner. We reported that RLXH2 significantly declined cellular toxicity and apoptosis associated with 177Lu-EDTMP in MG63 and Saos-2 cells through the notch-1 pathway.